Analisis Sistem Informasi Akuntansi (SIA) atas Siklus Pendapatan Rawat Inap Kamar VIP di Rumah Sakit Benyamin Guluh, Kabupaten Kolaka - Maya Latifah; Arnadi Chairunnas; Sabarudin Sabarudin (Jurnal Kendali Akuntansi, 2023)
Accounting is a process of recording, classifying, and concluding every financial transaction that occurs and is the main thing in the hospital's finance department. The finance department is also used as a reference by the directors in making policies and decisions. The existence of an Accounting Information System will make it easier for the finance department and other related parts such as cashiers and accounting to collect data. This study aims to determine whether the accounting information system for inpatient income at Benyamin Guluh Hospital, Kolaka Regency, is good or not. This type of research is a qualitative descriptive research while the processed data sources are secondary obtained through documents, notes, reports, archives and other supports according to the needs of the author. Data collection techniques are carried out by means of observation, interviews, and documentation which will be analyzed qualitatively and described in descriptive form. The results of the data analysis show that the organizational structure contained in the Benyamin Guluh Hospital, Kolaka Regency, has separated the duties and authorities of each work function. The procedures used are also in accordance with generally accepted standard operating procedures.